Breaking the poverty cycle the human basis for sustainable development - Pick de Weiss, Susan; Sirkin, Jenna (New York ; Oxford : Oxford University Press, 2010)
Pick and Sirkin show how IMIFAP, a Mexican NGO, has employed a development strategy to encourage the establishment of a participatory, healthy and educated citizenry.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Sustainable development; Poverty